Five-Year Journey of Technical Assistance in Health Governance Reforms: A Case Report - Yuniar, Popy; Trihandini, Indang; Muyassar, Ibnu; Khoiriyah, Latifatul; Minawati, Minawati; Birjaman, Fathiyya Aliyah; Diana, Tyra Septi; Serafina, Annabel; Putri, Hertina Raisa; Maimunah, Rana; Setiawan, Riko; Ramadhianisa, Nadazaira Alifia; Diyanto, Aris (UI Scholars Hub, 2025)
Many districts and cities in Indonesia continue to have Public Health Development Index scores below the national average, highlighting the need for improved health governance. This study assessed the five-year impact (2019–2023) of a mentoring program for 149 District Health Offices in preparing annual work plans, focusing on stagnation or performance declines. Using a qualitative approach, the study analyzed annual work plan scores before and after technical assistance, conducted focus group discussions, and carried out in-depth interviews to identify challenges. Key barriers included data management issues, weak advocacy, knowledge transfer gaps, and poor cross-sectoral coordination, which hindered decision-making and program sustainability. Findings suggested that structured technical assistance enhanced data-driven planning and intersectoral collaboration at the district level. Strengthening governance frameworks through capacity-building programs and integrating mentorship models into national health strategies can improve regional health performance.